In Vitro Screening of Soybean Genotypes under Salinity Stress - Hasan, M.K.; Nasiruddin, K.M.; Al-Amin, M.; Hossain, A.K.M.S. (International Journal of Applied Sciences and Biotechnology, 2016)
Salinity is one of the most limiting factors for successful crop production in in arid and semi-arid regions of the world. Thirty eight soybean genotypes were screened at 8mMNaCl under in vitro condition. Salinity reduced Shoot dry weight, Root dry weight and Plant height. Salt susceptibility index was fully and positive correlated with percent reduction of total dry weight. Principal component analysis showed that the first two components were extracted that comprises of about 98.6% of the total variation in the genotypes. Based on the K-means clustering, 8, 6, 12 and 12 genotypes were categorized under cluster II, IV, III and I and considered as tolerant, moderately tolerant, moderately susceptible and susceptible which represents the 21, 16, 31.5 and 31.5%, respectively. Genotypes Shohag, AGS 313, PK 416, AGS 66, MACS 57, AGS 195, GC 308, AGS 129 were found relatively tolerant to salinity. Int J Appl Sci Biotechnol, Vol 4(2): 207-212